O posicionamento do telejornalismo da TV Globo e Record no contexto da COVID-19 - Sanches, Raphael Leal de Oliveira (2023)
The daily journalism practices of the main tv news, Tv Globo and Tv Record, are the object of comparative study of this project: their news about the new wordwide surge of the coranavirus and the impact of this news coverage in the brazilian daily lives. This research uses mixed method research (qualitative and quantitative) to gain a more complete picture. The methodological procedures are about qualitative and quantitative analysis, case study, and the analysis of content of TV Globo and TV Record journalistic coverage of the first 14 months of COVID-19 pandemic in Brazil. March 23rd, 2019 is the initial date of the pandemic research with the establishment of the quarentine in the state of Sao Paulo (the first state to take social measures to stop the virus to spread) and the end of this research on May 31st - in order to include the beginning of COVID-19 vaccination in Brazil. In many diferent moments the present research uses comparative information between the two main brazilian TV news to illustrate the different and similar report positioning such as the political dissent between Jornal Nacional and Jornal da Record. The comparative information also illustrate how such political dissent affected the communication of risks during such pandemic creating confusion about social distancing either criticising the Government of the state of Sao Paulo for the measures taken or criticising the Brazilian Government for lack of actions that might have been taken. In another moment, the research highlights how the two mentioned TV news were heading towards a unity of speech concerning COVID-19 vaccination campaigns and the vaccinations. The study also addresses the audience and the rate of acceptance of both brazilian TV news and how their credibility was decreasing or wasn’t over time and what contributed to these changes.(AU)